The Orem Self-Care Based Protocol on Interdyalitic Weight Gain (IDWG) in Chronic Kidney Disease Hemodialysis Patients in the Hospital - Ahmad Faiq; Fery Agusman Motuho Mendrofa; Blacius Dedi (GLOBAL HEALTH SCIENCE GROUP, 2026)
Chronic Kidney Disease (CKD) is a health problem with increasing prevalence in Indonesia and globally. Patients with end-stage CKD generally undergo hemodialysis as replacement therapy, but this is often accompanied by complications such as Interdialytic Weight Gain (IDWG) due to excess fluid between dialysis sessions. Uncontrolled IDWG can lead to hypertension, pulmonary edema, and even heart failure. Therefore, effective nursing interventions are needed to help patients manage IDWG, one of which is through the application of Orem's Self-Care theory. This study aims to analyze the effectiveness of implementing the Orem Self-Care based protocol on IDWG in hemodialysis patients with chronic kidney failure at Dr. Loekmonohadi Hospital, Kudus. The study design used a quasi-experimental approach with a pre-test–post-test control group design . The sample consisted of 84 hemodialysis patients selected using a saturated sampling technique and divided into an intervention group (n=42) and a control group (n=42). Data collection was conducted by measuring the patients' Interdialytic Weight Gain (IDWG) before and after the intervention. The intervention included fluid management education, weight monitoring, and fluid restriction strategies. Data analysis was performed using a paired t-test and a test for differences between groups with a significance level of p < 0.05. Before the intervention, the majority of patients were unable to control their IDWG (88.1 % in the intervention group; 81.0% in the control group). After the intervention, 90.5 % of the intervention group achieved IDWG control compared to only 26.2% in the control group. The mean IDWG decreased from 4.99 kg to 3.14 kg, with a significant difference of 1.85 kg (p < 0.001). The Orem Self-Care based protocol is effective in reducing IDWG in hemodialysis patients with CKD, increasing patient independence, and potentially preventing complications due to fluid overload.